2020
DOI: 10.3389/fpsyg.2020.570048
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Effect of Emotional Labor: A Multi-Level Investigation in Front-Line Service Teams

Abstract: The main purpose of this study is to consider individuals in teams and to reexamine how emotional labor affects the performance of front-line service team and team members through emotional exhaustion. Multi-source data collection and a time-lagged research design was adopted to collect data from matched team members and customers nested in 82 front-line service teams in a large electronics provider based in China. The findings show that surface acting increases emotional exhaustion which reduces customer loya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 66 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…A study of Chinese hospital nurses by Deng et al [ 52 ] found that surface acting is positively associated with emotional exhaustion. Zhao et al [ 53 ] also confirmed in a study of front-line service teams that surface acting positively predicts emotional exhaustion. With this theoretical and empirical evidence, we expect the following:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 89%
“…A study of Chinese hospital nurses by Deng et al [ 52 ] found that surface acting is positively associated with emotional exhaustion. Zhao et al [ 53 ] also confirmed in a study of front-line service teams that surface acting positively predicts emotional exhaustion. With this theoretical and empirical evidence, we expect the following:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 89%
“…However, P3 showed no change in deep acting and P1 showed a decrease in deep acting (from 2 to 1.67), but this decrease was smaller than the decrease in surface acting (from 2.33 to 1). Deep acting, one aspect of emotional labor, requires effort to actually feel and express the required emotions, and some studies show that, unlike surface acting, deep acting is related to better mental health and high job satisfaction [21,22]. Thus, though P2 showed an increase in overall emotional labor level after the mindfulness program, given that deep acting was most affected, it is likely that the mindfulness program still had a positive effect on their mental health and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the nature of the investigation and its multiple advantages, the questionnaire was utilised as a data-collecting device in the study. The instrument was designed based on the works of experts in the field, such as Deng et al (2016), Ogunsola et al (2020) and Zhao et al (2020). In order to ensure the instruments' validity, we gave drafts to one Professor from the University of Cape Coast and one colleague at St. Joseph's College of Education for their expert judgments, which helped in proving the validity of the instruments.…”
Section: Issues Of Validity and Reliabilitymentioning
confidence: 99%